Prevalence and risk factors of metabolic dysfunction- associated steatotic liver disease in south Central Uganda: A cross-sectional survey - Enriquez, Rocio; Homsi, Mahmoud; Ssekubugu, Robert; Nabukalu, Dorean; Zeebari, Zangin; Marrone, Gaetano; Gigante, Bruna; Chang, Larry W; Reynolds, Steven J.; Nalugoda, Fred; Ekström, Anna Mia; Hagström, Hannes; et al. (Wiley Subscription Services, Inc, 2024)
Background: Despite numerous risk factors and serious consequences, little is known about metabolic dysfunction-associated steatotic liver disease (MASLD) at population level in Africa. Aim: The aim of the study was to estimate the prevalence and risk factors of MASLD in people living with and without HIV in Uganda. Methods: We collected data from 37 communities in South Central Uganda between May 2016 and May 2018. We estimated MASLD prevalence using the fatty liver index and advanced liver fibrosis using the dynamic aspartate-to-alanine aminotransferase ratio. We collected additional data on sociodemographics, HIV and cardiovascular disease (CVD) risk factors. We used multivariable logistic regression to determine the association between HIV, CVD risk factors and MASLD. Results: We included 759 people with HIV and 704 HIV-negative participants aged 35–49. MASLD prevalence was 14% in women and 8% in men; advanced liver fibrosis prevalence was estimated to be <1%. MASLD prevalence was more common in women (15% vs. 13%) and men (9% vs. 6%) with HIV. Being female (odds ratio [OR] = 2.1; 95% confidence interval [CI] = 1.4–3.3) was associated with a higher odds of MASLD after adjustment for confounders; HIV infection was borderline associated with MASLD (OR = 1.4; 95% CI: 1.0–2.0). Conclusions: In a relatively young cohort in Uganda, 14% of women and 8% of men had MASLD. There was an indication of an association between HIV and MASLD in multivariable analysis. These data are the first to describe the population-level burden of MASLD in sub-Saharan Africa using data from a population-based cohort.
Keywords: metabolic dysfunction; steatotic liver disease ;risk factors of MASLD in people living with and without HIV in Uganda; South Central Uganda